2017
DOI: 10.21764/efd.31545
|View full text |Cite
|
Sign up to set email alerts
|

Engelli̇ Çocuğa Sahi̇p Anneleri̇n Sosyal Destek Algilari: Psi̇koloji̇k Danişmanlarin Rolleri̇

Abstract: Bu çalışmanın amacı zihinsel engelli çocuğa sahip olan annelerin sosyal destek algıları ve annelerin çocuklarının gelecek planlamalarına ilişkin görüşlerinin incelenmesidir. Bu bağlamda zihinsel engelli çocukların devam ettiği eğitim kurumlarındaki psikolojik danışmanların rol ve sorumlulukları üzerinde durulmuştur. Bu amaçla Denizli Rehberlik ve Araştırma Merkezi'nden hizmet alan 11 engelli çocuk annesi ile nitel araştırma yöntemlerinden yarı yapılandırılmış görüşme yöntemiyle veri toplanmıştır. Görüşmeler se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…33 In Turkey, better communication with the child is more important than academic skills, and social support is especially essential from family and friends for wellbeing. 34,35 A negative relationship was observed between hopelessness levels of individuals and their perceived social support. Th is negative relation was also apparent in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…33 In Turkey, better communication with the child is more important than academic skills, and social support is especially essential from family and friends for wellbeing. 34,35 A negative relationship was observed between hopelessness levels of individuals and their perceived social support. Th is negative relation was also apparent in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study conducted by Toker, Başgül, and Özaydın (2019) with mothers of children with Down syndrome, the mothers stated that their close relatives provided the most social support, followed by their spouses and their children. In a qualitative study carried out by Arıcıoğlu and Gültekin (2017) on social support and future concerns of mothers of mentally retarded children, it was reported that mothers did not receive social support from their spouses, families or people outside the family. According to Boyd (2002), it was determined that mothers who did not receive support from their spouses experienced more stress.…”
Section: Discussionmentioning
confidence: 99%
“…According to Boyd (2002), it was determined that mothers who did not receive support from their spouses experienced more stress. Strengthening family functions is also an important factor in the social support received from the family (Arıcıoğlu & Gültekin, 2017). In a study conducted by Meral and Cavkaytar (2012) on perceived social support in families with children with autism, it was emphasised that social support was primarily from family, friends and the significant other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu düĢünce ile birlikte çocuklarına iliĢkin pek çok hayal kurmakta ve anne baba olmaktadırlar. Kurulan hayaller ise sağlıklı bir çocuk düĢüncesi ile ilgili olurken özel gereksinimli bir çocuğun hayatlarına girmesiyle beraber hayaller ve planlar değiĢmek zorunda kalmaktadır (Arıcıoğlu ve Gültekin, 2017). Özel gereksinimli bir çocuğa sahip olmak ailelerin hazırlıklı olmadıkları ve beklenmeyen zorluklar getiren bir süreci baĢlatmaktadır.…”
Section: Gġrġġunclassified